Enhancement of optoelectronic properties of ZnO thin films by Al doping for photodetector applications. (March 2021) - Doni Pon, V.; Joseph Wilson, K.S.; Hariprasad, K.; Ganesh, V.; Elhosiny Ali, H.; Algarni, H.; Yahia, I.S.
Abstract: In the present study, pure and Al-doped ZnO thin films have been deposited on glass substrates using a cost-effective nebulizer spray technique. The structural, topographical, photoluminescence, and UV detector properties of ZnO thin films have been studied for various aluminium-doping concentrations. X-ray diffraction (XRD) studies confirmed the polycrystalline hexagonal structure plane with preferred orientation along (002) direction. The ZnO structural parameters like crystallite size, dislocation density, and strain showing considerable variation with aluminium doping. Atomic force microscope (AFM) images displaying spherical grains and the grain size is increasing with Al concentration. The energy dispersive X-ray (EDX) analysis displays the presence of Zn, Al, and O elements in the deposited thin films. The optical bandgap values are decreased with aluminium doping concentration and the lowest value was observed for the 1% Al doping. Photoluminescence (PL) spectra reveal a sharp emission peak at 390 nm and peak with the shoulder at 554 nm. The Responsivity, External quantum efficiency, and Detectivity of pure and doped samples are in the range of 0.22–0.38 AW -1, 70–123%, and 1.22 × 10 10 to 1.70 × 10 10 Jones, respectively. The better photodetection results are observed for the 1% Al-doped ZnO thin film which indicates it is a good candidate for photo-detector applications. Highlights: Al doped ZnO thin films coated on glass substrates to enhance the photodetector performance. The Responsivity, External quantum efficiency, and Detectivity of pure and doped samples are in the range of 0.22–0.38 AW −1, 70–143%, and 1.22 × 10 10 to 1.70 × 10 10 Jones, respectively. The maximum photosensing property achieve for ZnO: Al(1%) thin film. It provides a low cost nebulizer spray pyrolysis method is suitable for fabrication of photodetector.